Somatosensory Cortex Repetitive Transcranial Magnetic Stimulation and Associative Sensory Stimulation of Peripheral Nerves Could Assist Motor and Sensory Recovery After Stroke - de Freitas Zanona, Aristela; Romeiro da Silva, Andressa Claudia; do Rego Maciel, Adriana Baltar; Gomes do Nascimento, Livia Shirahige; Bezerra da Silva, Amanda; Bolognini, Nadia; Monte-Silva, Katia (Frontiers in Human Neuroscience, 2022)
Background. We investigated whether transcranial magnetic stimulation (rTMS) over the primary somatosensory cortex (S1) and sensory stimulation (SS) could promote upper limb recovery in participants with subacute stroke. Methods. Participants were randomized into four groups: rTMS/Sham SS, Sham rTMS/SS, rTMS/SS, and control group (Sham rTMS/Sham SS). Participants underwent ten sessions of sham or active rTMS over S1 (10 Hz, 1,500 pulses, 120% of resting motor threshold, 20 min), followed by sham or active SS. The SS involved active sensory training (exploring features of objects and graphesthesia, proprioception exercises), mirror therapy, and Transcutaneous electrical nerve stimulation (TENS) in the region of the median nerve in the wrist (he stimulation intensity was determined as the minimum intensity at which the participants reported paresthesia), five electrical pulses of 1 ms duration each at 10 Hz were delivered every second over 45 min. Sham stimulations occurred as follows Sham rTMS: coil was held while disconnected from the stimulator, and rTMS noise was presented with computer loudspeakers with recorded sound from a real stimulation. The Sham SS received therapy in the unaffected upper limb, did not use the mirror and also received TENS stimulation for only 60 seconds. The primary outcome was the Body Structure/Function: Fugl-Meyer Assessment (FMA) and Nottingham Sensory Assessment (NSA); the secondary outcome was the Activity/Participation domains, assessed with Box and Block Test, Motor Activity Log scale, Jebsen-Taylor Test, and Functional Independence Measure. Results. Forty participants with stroke ischemic (n=38) and hemorrhagic (n=2), men (n=19) and women (n=21), in the subacute stage (10.6±6 weeks) had a mean age of 62.2±9.6 years, were equally divided into four groups (10 participants in each group). Significant somatosensory improvements were found in participants receiving active rTMS and active SS, compared with those in the control group (sham rTMS with sham SS). Motor function improved only in participants who received active rTMS, with greater effects when active rTMS was combined with active SS. Conclusion. The combined use of SS with rTMS over S1 represents a more effective therapy for increasing sensory and motor recovery, as well as functional independence, in participants with subacute stroke